2019
DOI: 10.5195/jyd.2019.720
|View full text |Cite
|
Sign up to set email alerts
|

Life Skill Development and Financial Impact Associated With a Youth Livestock Sales Program

Abstract: The Sale of Junior Champions is a premier livestock auction and youth scholarship program held at Dixie Nationals as a part of Mississippi’s junior livestock program. The sale is open to 4-H and FFA members who qualified their livestock at the annual Dixie National Junior Round-Up. While youth livestock sales programs are commonly found at state and county fairs throughout the United States, demographic information and information concerning financial and life skill impacts of the program on participants is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…While not significant, the biggest change in CRC-PIE participants seen in emotional safety scores for the current study was in the category of self-esteem; thus, these scores could be reflective of skill development as a product of the PIE sessions. As for other emotional safety categories warranting further investigation, although respect was a category of emotional safety that showed minimal change within this study, Evans et al [67] reported improvement in respect when assessing skill development associated with a youth livestock program. Development of skills indicates the ability to learn and, thus, cognitive function.…”
Section: Human Physiological and Behavioral Responsesmentioning
confidence: 67%
“…While not significant, the biggest change in CRC-PIE participants seen in emotional safety scores for the current study was in the category of self-esteem; thus, these scores could be reflective of skill development as a product of the PIE sessions. As for other emotional safety categories warranting further investigation, although respect was a category of emotional safety that showed minimal change within this study, Evans et al [67] reported improvement in respect when assessing skill development associated with a youth livestock program. Development of skills indicates the ability to learn and, thus, cognitive function.…”
Section: Human Physiological and Behavioral Responsesmentioning
confidence: 67%